2019
DOI: 10.3928/24748307-20181127-01
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Cervical Cancer Screening Among Mexican-American Women

Abstract: Background: Health literacy is a requisite skill for making personal health and health care decisions. Low health literacy may contribute to lower cervical cancer screening rates and cervical cancer health disparities among Mexican-American women in South Texas. Objective: To explore older Mexican-American women's health literacy related to cervical cancer from the perspective of Zarcadoolas, Pleaseant, and Greer's health literacy model. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Tyler is an underserved rural area with an estimated population size of around 105,729 people [23]. Moreover, due to the lack of health literacy and related awareness, particularly among the uninsured minorities as demonstrated in other studies [24,25], limited visits could occur in the clinic for cervical health checkups. Another limitation is the lack of comprehensive follow-up data, which stemmed from the limited number of visits by the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Tyler is an underserved rural area with an estimated population size of around 105,729 people [23]. Moreover, due to the lack of health literacy and related awareness, particularly among the uninsured minorities as demonstrated in other studies [24,25], limited visits could occur in the clinic for cervical health checkups. Another limitation is the lack of comprehensive follow-up data, which stemmed from the limited number of visits by the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Human Papillomavirus also known as HPV is a non-enveloped, double-stranded, circular DNA virus that has been proven to be a leading factor in the development of cervical cancer in women (3). HPV has over 100 subtypes identified, and from those 100 there are many subtypes that are specifically associated with the development of cervical cancer some of them being subtypes 16,18,31,33,35,45,52, and 58 (4) For example, HPV 16 has been shown to affect the genomes of the host (13). Even though HPV is not genetically inherited, recent studies have discovered the variant to be transmitted naturally.…”
Section: Risks Human Papillomavirusmentioning
confidence: 99%
“…In addition to the high prevalence of cervical cancer in Hispanic women, culture and social factors contribute to the lack of understanding of the disease. Due to the lack of understanding of the disease, families and caretakers are unable to communicate and provide awareness about the importance of getting tested (18). The Latina women's stigma of privacy especially when it comes to certain healthcare practices is a big factor, therefore putting them at risk (18).…”
Section: Culturementioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that poor health literacy is an important barrier to cancer screening adherence [12][13][14][15]. Although studies have identified the impact of social determinants of health, such as cultural beliefs, health literacy and language on disparities in cancer screening rates among minority populations [16][17][18], there is substantial evidence that health literacy is a complex, multidimensional construct that cannot be measured using generic measures that do not address different domains related to management of specific chronic diseases such as cancer [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%